Role of methionine adenosyltransferase 2A in bovine preimplantation development and its associated genomic regions - Shuntaro Ikeda (Nature Portfolio, 2017)
Abstract Methionine adenosyltransferase (MAT) is involved in folate-mediated one-carbon metabolism, which is essential for preimplantation embryos in terms of both short-term periconceptional development and long-term phenotypic programming beyond the periconceptional period. Here, our immunofluorescence analysis of bovine oocytes and preimplantation embryos revealed the consistent expression of MAT2A (the catalytic subunit of the ubiquitously expressed-type of MAT isozyme) during this period. Addition of the MAT2A inhibitor FIDAS to the culture media of bovine preimplantation embryos reduced their blastocyst development, revealing the particular importance of MAT2A in successful blastocyst development. Exploration of MAT2A-associated genomic regions in bovine blastocysts using chromatin immunoprecipitation and sequencing (ChIP-seq) identified candidate MAT2A-associated genes implicated not only in short-term periconceptional embryo development, but also in long-term phenotypic programming during this period in terms of growth, metabolism, and immune functions. These results suggest the critical involvement of MAT2A in the periconceptional period in life-long programming of health and disease as well as successful preimplantation development.